Assessing the Effects of Multiple Stressors on Aquatic Systems across Temporal and Spatial Scales: From Measurement to Management - Segurado, Pedro; Branco, Paulo; Ferreira, Maria Teresa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is focused on the interplay of multiple stressors in aquatic systems and its consequences for management across spatial and temporal scales. It is organized into six case studies from four continents (Europe, Oceania, Africa, and North America), each based on several different data sources (field and experimental data, historical data, literature reviews, inquiries, and expert knowledge). The case studies address the joint effects of a variety of stressors (physical and chemical barriers, hydromorphology, temperature, drought, and water quality) on a diversity of biological response indicators (fish, macroinvertebrates, and phytoplankton) and discuss the main implications for managing aquatic ecosystems more effectively.